Efektivitas Strategi Think Talk Write terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Cahyaningrum, Indri; Husna, Asmaul; Gusmania, Yesi (Edumatika, 2020)
The purpose of this research is to test effectivitytrategy Think Talk Write (TTW) of the ability of problem solving mathematical, and test whether the differences efektivity between strategy Think Talk Write (TTW) with determine saintific of the ability of problem solving mathematical students. The kind of research this quasi his experiments with design research posttest only control group design. Population in research it is a whole students grade VIII of SMP Negeri 34 Batam which consisted of 279 students which are divided into 7 class. echnique the sample researchers used was purposive sampling, where samples selected on a consideration of the principal and math teacher and chosen class VIII G as a class experiment and class VIII E as a class control with 39 students in each class. An instrument used research it will be a test the discussion as much as 4 about that has been tested validitas, reliability, the standart hardship and capacity classification. Based on researchers sig.(2-tailed) = 0.028 < 0.05 and sig.( 2-tailed ) 0.013 < 0.05. So that can be concluded Think Talk Write (TTW) effective in the ability of problem solving mathematical students and there is a difference effectivity between strategy Think Talk Write (TTW) with determine saintific of the ability of problem solving mathematical students.